In Vitro Activity of Netilmicin Compared with Gentamicin, Tobramycin, Amikacin, and Kanamycin - Eickhoff, Theodore C. (1977)
The in vitro activity of netilmicin was compared with that of gentamicin, tobramycin, amikacin, and kanamycin against 636 strains of bacteria recently isolated from clinical sources. Gentamicin was the most active antibiotic, but netilmicin and tobramycin closely paralleled it. Netilmicin was generally four-to eightfold less active than gentamicin against Serratia and group A streptococci, and was twofold less active against Pseudomonas aeruginosa. When effects of inoculum size and concentration of divalent cations in the media were evaluated, netilmicin was shown to be similar to gentamicin in vitro. Minimum inhibitory concentrations for P. aeruginosa were increased as much as 18-fold when the Mg(2+) and Ca(2+) concentrations were increased to physiological levels in Mueller-Hinton broth.